Preparing Resident Physicians to Protect Immigrant Patient Rights During Immigration Enforcement Encounters: A Pre–Post Educational Intervention - Simran Rahi; Safia Ansari; Emily Gordon (Journal of Immigrant and Minority Health, 2026)
Abstract Immigration enforcement increasingly intersects with healthcare delivery, creating clinical situations that may affect immigrant patients’ access to care, trust in healthcare institutions, and interactions with physicians. Despite these challenges, formal training on immigrant patient rights and physician responsibilities during immigration enforcement encounters remains limited. We evaluated the impact of a case-based educational intervention on resident physician preparedness for these encounters. We conducted a pre–post educational intervention study at an urban academic teaching hospital serving a diverse immigrant population. Resident physicians participated in a 60-minute curriculum addressing immigrant patient rights, physician confidentiality obligations, emergency care requirements, distinctions between administrative and judicial warrants, and practical responses to immigration enforcement encounters. Anonymous electronic surveys administered immediately before and after the intervention assessed knowledge and confidence. Among 190 eligible residents, 58 residents completed the pre-intervention survey and 49 completed the post-intervention survey. Following the intervention, residents demonstrated significant improvements in knowledge of legal protections relevant to immigrant patient care and increased confidence in educating patients about their rights, protecting patient confidentiality, and interacting with immigration enforcement agents. Qualitative responses emphasized the curriculum’s immediate clinical applicability while identifying the need for institution-specific policies, communication scripts, and leadership guidance. Educational interventions addressing immigration enforcement encounters may improve physician preparedness for caring for immigrant patients while complementing institutional efforts to promote equitable, patient-centered care.